An Analysis on the Experimental Design of “My Money or Yours: House Money Payment Effects" - Berticelli de Freitas, Abilio Henrique (Journal of Economics and Behavioral Studies, 2022)
Considering the expanding usage of experiments in Economics, the present article chooses one published paper in the area, dealing with the house money effect, and analyzes it in a didactic way as concepts relating to the experimental design of lab experiments are evoked and discussed. In order to do so, three sections are outlined. First of all, the house money effect is explained and the article under scrutiny is placed in the context of what had already been done before; secondly, some of the experimental design concepts are summarised and then applied to soundly describe the experimental design of their experiment. Finally, after briefly presenting their results, there is an analytical overview of what has been done after their work and a personal take on possible lines for further research.